Exploring EFL pre-service teachers’ perceptions of loving pedagogy in the teaching practicum - Gabriella Nur Shafa; Hamamah Hamamah; Roosi Rusmawati; Putu Dian Danayanti Degeng (Universitas Muhammadiyah Malang, 2025)
This research aims to explore how EFL pre-service teachers apply loving pedagogy during their teaching practicum to build emotional connections with students and support their learning. Loving pedagogy is a teaching approach based on care, empathy, and strong teacher-student relationships. It creates a classroom environment where students feel respected, safe, and motivated. In the Indonesian context, where bullying remains a concern in many schools, the use of loving pedagogy can help reduce negative behavior and promote student well-being. This research used a quantitative case study design allowed for an investigation of a specific group within educational context. This study employed purposive sampling, with 112 EFL pre-service teachers selected through a questionnaire adapted from the Loving Pedagogy Scale. The scale includes four main aspects: kindness and empathy, intimacy and bonding, sacrifice and forgiveness, and community and acceptance. The results among the aspects of loving pedagogy showed that the highest score was in the community and acceptance aspect, with accepting diversity receiving a mean of 3.89, reflecting a strong commitment by EFL pre-service teachers to inclusivity. Another high score aspect was kindness and empathy, where classroom rule adherence appreciation had a mean of 3.64, indicating that teachers highly value student effort and achievement in class. This research recommends applying loving pedagogy to improve student-teacher interactions and create a better learning environment. It also encourages EFL pre-service teachers to reflect on their teaching style and develop it to be more caring and thoughtful educators.